The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1550-7408.2001.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Biochemical and Molecular Characterization of Herpetomonas samuelpessoai camargoi n. subsp., a Trypanosomatid Isolated from the Flower of the Squash Cucurbita moschata

Abstract: We report the morphological, biochemical and molecular characteristics of a trypanosomatid isolated from the flower of Cucurbita moschata. Although the trypanosomatid was isolated from a plant, the lack of recognition of Phytomonas-specific molecular markers based on spliced-leader and ribosomal genes as well as by monoclonal antibodies specific for Phytomonas argues against assigning it to this genus. Because the isolate displayed typical opisthomastigote forms in culture, it is assigned to the genus Herpetom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(68 reference statements)
0
15
0
5
Order By: Relevance
“…Several studies have shown that plants can harbor trypanosomatids of various genera besides Phytomonas [7,14,15,20,26]. In contrast to Phytomonas, for which speci¢c molecular taxonomic markers are available [7,14,15], classi¢cation of members of Herpetomonas, Leptomonas and Crithidia still requires the development of speci¢c methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that plants can harbor trypanosomatids of various genera besides Phytomonas [7,14,15,20,26]. In contrast to Phytomonas, for which speci¢c molecular taxonomic markers are available [7,14,15], classi¢cation of members of Herpetomonas, Leptomonas and Crithidia still requires the development of speci¢c methods.…”
Section: Discussionmentioning
confidence: 99%
“…So far, all isolates from phloem have been classi¢ed as Phytomonas, whereas the few isolates from latex and fruits were classi¢ed as Leptomonas and Crithidia [7,11,14]. The only available culture of trypanosomatids isolated from £owers was classi¢ed as Herpetomonas [20]. However, despite the generic polymorphism of plant trypanosomatids, most plant isolates continue to be classi¢ed as Phytomonas exclusively on the basis of host origin, with only ¢ve plant isolates classi¢ed into other genera thus far [4,7,14,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After careful revision, it now represents a monophyletic assemblage comprising 13 species, some of which exhibit extreme morphological polymorphisms. In general, Herpetomonas are found as parasites of dipterans, but they have been reported also from predator hemipterans [14], plants [15,16], rats [6], and immunocompromised humans [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Das 97 culturas analisadas, 41 já haviam sido identificadas como Phytomonas em estudos anteriores (Teixeira et al, 1996;Serrano et al, 1999b,c (Serrano et al, 1999a,b;Catarino et al, 2001;Fiorini et al, 2001). Infecções experimentais demonstraram que tripanossomatídeos de diversos gêneros além de Phytomonas se desenvolvem muito bem em tomates Camargo, 1999).…”
Section: Diagnóstico De Phytomonas Em Culturas De Tripanossomatídeos unclassified